Cardiac sympathetic innervation network shapes the myocardium by locally controlling cardiomyocyte size through the cellular proteolytic machinery. (17th June 2019) - Pianca, Nicola; Di Bona, Anna; Lazzeri, Erica; Costantini, Irene; Franzoso, Mauro; Prando, Valentina; Armani, Andrea; Rizzo, Stefania; Fedrigo, Marny; Angelini, Annalisa; Basso, Cristina; Pavone, Francesco S.; et al.
Abstract : Key points: The heart is innervated by a dense sympathetic neuron network which, in the short term, controls chronotropy and inotropy and, in the long term, regulates cardiomyocyte size. Acute neurogenic control of heart rate is achieved locally through direct neuro‐cardiac coupling at specific junctional sites (neuro‐cardiac junctions). The ventricular sympathetic network topology is well‐defined and characteristic for each mammalian species. In the present study, we used cell size regulation to determine whether long‐term modulation of cardiac structure is achieved via direct sympatho‐cardiac coupling. Local density of cardiac innervation correlated with cell size throughout the myocardial walls in all mammalian species analysed, including humans. The data obtained suggest that constitutive neurogenic control of cardiomyocyte trophism occurs through direct intercellular signalling at neuro‐cardiac junctions. Abstract: It is widely appreciated that sympathetic stimulation of the heart involves a sharp increase in beating rate and significant enhancement of contractility. We have previously shown that, in addition to these evident functions, sympathetic neurons (SNs) also provide trophic input to cardiomyocytes (CMs), regulating cell and organ size. More recently, we have demonstrated that cardiac neurons establish direct interactions with CMs, allowing neuro‐cardiac communication to occur locally, with a 'quasi‐synaptic' mechanism. Based on the evidence that cardiac SNs are unevenly distributed throughout the myocardial walls, we investigated the hypothesis that CM size distribution reflects the topology of neuronal density. In vitro analyses of SN/CM co‐cultures, ex vivo confocal and multiphoton imaging in clarified hearts, and biochemical and molecular approaches were employed, in both rodent and human heart biopsies. In line with the trophic effect of SNs, and with local neuro‐cardiac communication, CMs, directly contacted by SNs in co‐cultures, were larger than the non‐targeted ones. This property reflects the distribution of CM size throughout the ventricles of intact mouse heart, in which cells in the outer myocardial layers, which were contacted by more neuronal processes, were larger than those in the less innervated subendocardial region. Such differences disappeared upon genetic or pharmacological interference with the trophic SN/CM signalling axis. Remarkably, CM size followed the SN distribution pattern in other mammals, including humans. Our data suggest that both the acute and chronic influence of SNs on cardiac function and structure is enacted as a result of the establishment of specific intercellular neuro‐cardiac junctions. Key points: The heart is innervated by a dense sympathetic neuron network which, in the short term, controls chronotropy and inotropy and, in the long term, regulates cardiomyocyte size. Acute neurogenic control of heart rate is achieved locally through direct neuro‐cardiac coupling at specific junctional sites (neuro‐cardiac junctions). The ventricular sympathetic network topology is well‐defined and characteristic for each mammalian species. In the present study, we used cell size regulation to determine whether long‐term modulation of cardiac structure is achieved via direct sympatho‐cardiac coupling. Local density of cardiac innervation correlated with cell size throughout the myocardial walls in all mammalian species analysed, including humans. The data obtained suggest that constitutive neurogenic control of cardiomyocyte trophism occurs through direct intercellular signalling at neuro‐cardiac junctions.